Hypertension and the Risk of Dementia - Sierra, Cristina (Frontiers in Cardiovascular Medicine, 2020)
Chronic hypertension, particularly midlife high blood pressure, has been associated with an increased risk of cognitive decline and dementia, including Alzheimer disease. However, these associations are complex and not fully elucidated. Cerebral small vessel disease emerges as one of the most important causes. Several observational studies have shown the potential beneficial role of antihypertensive therapy in preventing cognitive decline. However, randomized clinical trials have shown controversial results without proving nor disproving the association. On the other hand, in very elderly or frail people some studies have shown an association between low blood pressure and worse cognitive function. The optimal systolic and diastolic blood pressure values for protecting cognitive function, especially in elderly people, are not known.